Der nordische Fremde: Historische Untersuchung des medialen Schwedenbildes im Heiligen Römischen Reich (1500–1721) - Hämmerle, Tobias E. (Nordlit, 2020)
Until to the beginning of the 17th century the North was rather an unknown and abstract space for the average German-speaking recipient of early modern mass media (for example illustrated broadsheets, newspapers, pamphlets). In the course of the 17th century due to Denmark’s and Sweden’s participation in the Thirty Years War, the northern regions became a central topic in the early modern mass media and therefore forced the recipient to be more aware of it. In the course of the second half of the 17th century the northern kingdoms became less important for the publicists in the Holy Roman Empire and instead they laid their focus on the politics of French and the Ottoman Empire. Thus, the image of the northerners and their stereotypes, which had been introduced to the German speaking readers in the course of the Thirty Years War, lived on until the beginning of the 18th century. Nevertheless, the Great Northern War (1700–1721) brought the people from the northern regions back to the media landscape of the Holy Roman Empire and about the same time the illustrated broadsheet – an almost antiquated genre of mass media that had struggled with the upcoming of the new modern genre ‘newspaper’ – experienced a kind of a renaissance. The aim of this article is to describe how the northern region, with a focus on Sweden, was depicted in early modern mass media between the 15th and the 18th centuries. I will show continuities and changes of the visual and textual representation of ‘northerners’ and ‘Sweden’ in early modern mass media, which were published in the Holy Roman Empire between around 1500 until the end of the Great Northern War in 1721.